Trickle Down Efeck dan Perubahan Wajah Masjid di Yogyakarta - Pajar Hatma Indra Jaya (State Institute of Islamic Studies (IAIN) Salatiga, 2018)
In the last ten years, mosques in Yogyakarta are seen to be changing. This article aims at illustrating the changes and explaining the possible causes of the changes. In order to get the answers to such objectives, the researcher randomly searched for mosques in Yogyakarta that had innovative programs. Data showed that Jogokaryan mosque becomes the inspiration for the changes of mosques in Yogyakarta. The development of Jogokaryan mosque has become a “trickle down effect” that affects the revitalization of mosques in Yogyakarta. The concept to always make zero financial balance has raised awareness of the fact that so far infaq has not been spent optimally, while infaq should be used to accommodate the needs of those who make use of mosques. In fact, the spirit of making zero balance has encouraged the creativity of takmir (people involved in mosque management) to provide the best facilities for the worshippers. As a result, mosques in Yogyakarta are becoming more innovative in providing services for worshippers, both related to any services that are directly associated with prayer and related to services for those who are economically poor